Is there an election cycle in public employment? Separating time effects from election year effects - Matz Dahlberg; Eva Mörk (Uppsala University, Department of Economics, 2008)
Do governments increase public employment in election years? This paper investigates this question by using data from Sweden and Finland, two coun¬tries that are similar in many respects but in which local elections are held at different points in time. We can thereby separate an election effect from other time effects. Our results indicate that there is a statistically significant election year effect in local public employment, a production factor that is highly visi¬ble in the welfare services provided by the local governments in the Scandina¬vian countries. The effect also seems to be economically significant; the municipalities employ 0.6 more full-time employees per 1,000 capita in election years than in other years (which correspond to an increase by approximately 1 percent).
urn:nbn:se:uu:diva-15977
Keywords: D72; H72; P16; 330; Election cycle; Public employment; Exogenous elections; Wahl; Beschäftigungseffekt; Öffentlicher Dienst; Neue politische Ökonomie; Finnland; Schweden